The anatomy of the obturator nerve and its branches in a South African cadaver sample - Zithulele N. Tshabalala, PhD (Anatomy); René Human-Baron, PhD (Biosystems); Soné van der Walt; Elizabeth M. Louw; Albert-Neels van Schoor (Elsevier, 2022)
Purpose: Several surgical and clinical procedures are performed in the area of the medial compartment of the thigh. This places the obturator nerve and its branches in potential danger of injury. This study aimed to provide a clear description of the anatomy and course of the obturator nerve and its branches. Methods: One hundred and one formalin-fixed cadavers were dissected just lateral to the lumbar vertebra to describe the origin and course of the obturator nerve, as well as its relation to other anatomical structures. The location of the obturator nerve within the obturator foramen was quantified by measuring the distance from three bony landmarks of the obturator foramen to the nerve. Findings: In 20% of cases the obturator nerve originated from L3 and L4 rather than L2 to L4 in the combined sample. The bifurcation of the nerve occurred intrapelvically in 2% of cases, within the obturator canal in 93% of cases and extrapelvically in 5% of the sample. Regarding the course in the abdomen, the L3 root joined the L4 root more distally after exiting the psoas major muscle. In all cases on the left (n = 97) and 99% on the right, the anterior branch innervated the muscles of the medial thigh, in one case on the right the anterior branch innervated the pectineus muscle. The posterior branch assisted the anterior branch in the innervation adductor brevis in 10% on the left and 11% on the right sides. Conclusion: The results of this study may be used in the pre-operative preparation of surgeons that are to perform surgery in the area of the obturator foramen such as obturator nerve blocks for pain relief of adductor muscle contractions, prevention of adduction of the thigh during transurethral bladder surgery, additional analgesia after knee surgery, chronic hip pain, as well as postoperative analgesia after hamstring harvest for anterior cruciate ligament reconstruction.